Hepatitis C, Treatment and Drug Use in Australian Prison Settings - Fetherston, James Andrew (Curtin University, 2021)
This thesis examined issues surrounding the hepatitis C virus (HCV), its treatment, and injecting drug use as the principal risk factor for infections in Australian prison environments. Quantitative and qualitative data was collected from both former and current prisoners to explore knowledge and attitudes towards treatment. Additional data concerning drug use was collected via existing national surveys. Epidemic modelling was used to determine the potential of increased prisoner engagement in treatment.